2007
DOI: 10.1080/10901020701686609
|View full text |Cite
|
Sign up to set email alerts
|

Who is a Good Early Childhood Educator? A Critical Study of Differences within a Universal Professional Identity in Early Childhood Education Preparation Programs

Abstract: This article reports on a qualitative research project that examined ways in which pedagogical discourses within an early childhood education college preparation program construct a universal identity of the "good early childhood educator." Drawing upon theoretical explanations of the concept of difference in professional identification, a discursive analysis of the research participants' views indicates that the good early childhood educator is, on the whole, perceived as possessing a single, normative identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 12 publications
2
41
0
Order By: Relevance
“…Previous studies (e.g., Langford, 2007;Moles, 2014) have suggested that immigrant and refugee students appear to succumb to this pressure to conform, and Geena confided that she, too, felt a sense of obligation to the authoritative discourse: (interview, February 28, 2013) Power is infused with tension in cases where belonging in the community means losing the ability to negotiate and contribute to the terms of membership. Potential outcomes include feelings of powerlessness, vulnerability, and marginality (Wenger, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (e.g., Langford, 2007;Moles, 2014) have suggested that immigrant and refugee students appear to succumb to this pressure to conform, and Geena confided that she, too, felt a sense of obligation to the authoritative discourse: (interview, February 28, 2013) Power is infused with tension in cases where belonging in the community means losing the ability to negotiate and contribute to the terms of membership. Potential outcomes include feelings of powerlessness, vulnerability, and marginality (Wenger, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one student with a well-established identity as a leader and holder of knowledge in her cultural community shared that she struggled to make sense of the program content since "the things I knew are not here" (p. 173). When Langford (2007) interviewed instructors and analyzed textbooks and student assignments, she found that Canadian instructors utilized child development theory to quash diverse students' own cultural and linguistic knowledges. The diverse student, Langford claims, appears to be "viewed as less competent (and thus is more marginalized) because first she must learn discourses that are assumed to be commonsense, and second she must shed cultural and material practices (such as teacherdirection) incompatible with those of the good ECE" (Langford, 2006, p. 118).…”
Section: Culturally and Linguistically Diverse Ecte Students And Educmentioning
confidence: 99%
“…We find antecedents of this conception in the traditional feminine notion of "niceness," of the timid female virtue so alive and well in the gender ghetto that remains in early childhood education in many societies, including North America. Here, I am referring to the professional identity that commonly populates the imaginaries of who an early childhood educator is-the "Lady Bountiful" teacher (Harper & Cavanaugh, 1994)-who is most often female, gracious, nurturing, loving, and ready to inculcate children with a particular set of social and moral norms (see Langford, 2007;Meiners, 2002). Women "do" early childhood education, and thus traditional "female" virtues continue to find fertile ground in these practices.…”
Section: Happy Tales and Their Politics Of Nicenessmentioning
confidence: 99%
“…While previous studies have enquired into aspects of immigrant/refugee women's studies in ECTE programs (e.g. Gupta, 2013;Langford, 2007;Massing, 2015;Wilgus, 2013), little attention has been given to the modes of delivery in the program (Exposito & Bernheimer, 2012). We contend that the immigrant/refugee students in such programs are not only confronted with the dominant discourse of ECTE, but also with thoroughly established technological ways of conveying the (western/scientific) knowledge and skills they are expected to acquire.…”
mentioning
confidence: 93%